HUBUNGAN JENIS KELAMIN DAN BIDANG STUDI DENGAN PRAKTIK PENCEGAHAN DIABETES MELLITUS TIPE 2 PADA MAHASISWA (Studi Pada Mahasiswa Universitas Diponegoro Semarang) - Tutut Okta Hardiyanti; Arie Wurjanto; Nissa Kusariana; Retno Hestiningsih (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2021)
Diabetes mellitus type 2 is the most common cases, which is 90% of diabetes mellitus cases. Diabetes mellitus type 2 is a metabolic disorder characterized by high blood sugar levels due to damage to insulin secretion or a lack of insulin receptors so that it is difficult for glucose to enter the cells. College students should be agents of change that can help the government in efforts to prevent non-communicable diseases in Indonesia such as type 2 diabetes mellitus. Factors related to the practice of preventing type 2 diabetes mellitus in students need to be known, so that efforts to prevent diabetes mellitus can be carried out effectively. A study states that the factors related with the practice of preventing diabetes mellitus type 2 are gender and field of study. The aim of this study was to analyze the relationship between gender and field of study with the prevention practice of diabetes mellitus type 2 in Diponegoro University students in Semarang. This study conducted using a quantitative observational study methods with cross-sectional approach. The sample in this study was 407 undergraduate students of Diponegoro University. The sampling technique used in this study is the Nonprobability Sampling technique. This study uses a questionnaire to determine the variables studied. The results of this study showed a significant relationship between gender (p-value= 0.05) and the field of study of respondents (p-value= 0.00) and the practice of preventing diabetes mellitus type 2.